Analysis of the Protection of Children’s Rights in Family Disputes through Regulatory and Institutional Synergies with a Justice Perspective - Sugiono, Sugiono; Suwito, Suwito; Mujito, Mujito (Journal of Social Science Studies, 2023)
This study analyses legal protection for children in family disputes in Indonesia through a literature review using a thematic synthesis method. The analysis focuses on key regulations such as the Marriage Law and the Child Protection Law, including discussions on the involvement of religious courts, the Indonesian Child Protection Commission (KPAI), and civil society organisations. The results of the study identify various problems in practice, including the dominance of parental interests, weak involvement of experts, low participation of children, and gaps between legal norms and implementation in the field. The supervision system and enforcement mechanisms are not yet fully effective, so that children’s rights are often neglected after a verdict. The application of the principle of "the best interests of the child" must continue to be strengthened through training for law enforcement officials and the provision of psychosocial support services, family education, and community-based protection models. This study emphasizes the importance of comprehensive family law reform, institutional capacity building, and multi-stakeholder collaboration to achieve dignified, fair, and sustainable child protection. By strengthening regulations, optimizing inter-agency synergy, and building a child-friendly legal culture, the family law protection system can be more responsive to the dynamics of contemporary society.